Simulation of single-phase inverter operation using single phase matrix converter topology / Masnie Lalu - Lalu, Masnie (2009)
In this report the Single-phase Matrix Converter (SPMC) is presented to operate as an inverter. The well-known Sinusoidal Pulse Width Modulation (SPWM) technique was used to synthesize the output waveform. Safe commutation strategy was implemented to avoid voltage spikes due to inductive load. The development of a computer simulation model using MATLAB/Simulink is presented to verify the behavior of single-phase inverter operation using single phase matrix converter.